1990
DOI: 10.1111/j.1151-2916.1990.tb07589.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β‐Silicon Carbide by Silicon‐29 Solid‐State NMR, Transmission Electron Microscopy, and Powder X‐ray Diffraction

Abstract: Increased interest in ceramic materials, particularly for high-temperature, high-stress applications, has created the need for rapid and reliable analytical techniques to monitor microcrystalline structure of commercial ceramic powders. A comparative evaluation of commercially available PSiC powders is undertaken to analyze the potential of nuclear magnetic resonance (NMR) in the characterization of PSiC powder. NMR provides an acceptable, rapid method for characterization of powders both during powder manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…The signal at approximately −48 ppm corresponds to the reported chemical shift for Si 3 N 4 (−48.5 ppm). 59 The signal at −16 ppm and the shoulder at −20 ppm appear to be similar to the chemical shifts for β-SiC (−16.3 ppm) 60 and 2H-SiC (−20.0 ppm). 61 In the Raman spectrum of the residue, two bands are observed at 1337 and 1595 cm −1 , which are consistent with the Raman spectrum of amorphous carbon.…”
Section: Characterizations Of the Residue Pyrolyzed At 1700mentioning
confidence: 70%
“…The signal at approximately −48 ppm corresponds to the reported chemical shift for Si 3 N 4 (−48.5 ppm). 59 The signal at −16 ppm and the shoulder at −20 ppm appear to be similar to the chemical shifts for β-SiC (−16.3 ppm) 60 and 2H-SiC (−20.0 ppm). 61 In the Raman spectrum of the residue, two bands are observed at 1337 and 1595 cm −1 , which are consistent with the Raman spectrum of amorphous carbon.…”
Section: Characterizations Of the Residue Pyrolyzed At 1700mentioning
confidence: 70%
“…[5][6][7] Although TEM techniques have been instrumental in establishing this correlation, determining the average distribution of stacking errors in the starting powders or monitoring changes in error distribution/polytypic transformations during sintering can be tedious, if not practically impossible, using TEM. Carduner et al 8 recently reported a correlation between stacking disorder and features in NMR spectra, and demonstrated the applicability of NMR techniques in gaining qualitative information about stacking disorder in SiC. The present paper illustrates the utility of our simulation model in gaining qualitative information about the spatial distribution of stacking errors from XRD patterns, which can complement information obtained from NMR.…”
Section: Introductionmentioning
confidence: 75%
“…To further investigate the polytypes of SiC in the SiBCN powders, 29 Si solid-state NMR studies were introduced. Previous 29 Si solid-state NMR studies have outlined the relationship of the spectra to phase properties of SiC [18][19][20][21][22]. Typically, a single resonance line is observed in the spectrum of b-SiC while up to three closely spaced resonances characterize the a-SiC materials.…”
Section: Microstructure Of the Cs And CD Samplesmentioning
confidence: 97%